City of Caesar, City of God : Constantinople and Jerusalem in Late Antiquity. - Klein, Konstantin M. (Millennium-Studien / Millennium Studies, 2022)
Millenniumpursues an interdisciplinaryapproach transcending historical eras. The international editorial board and the advisory board represent a wide range of disciplines - contributions from art and literary studies are just as welcome as historical, theological and philosophical disciplines; contributions onLatin and Greek cultures just as welcome as on Oriental cultures.